Amiodarone-induced thyroid dysfunction in a tertiary center in south Brazil - Schaan,Beatriz D. (2005)
Amiodarone, used in the treatment of cardiac arrhythmias, is associated with thyroid dysfunction. No reports exist on its frequency in southern Brazil, nor studies evaluating the usefulness of clinical scores to diagnose thyroid abnormalities in these patients. This study aimed at determining the prevalence of amiodarone-induced thyroid dysfunction in a representative sample from a tertiary center, to study the conditions associated to this dysfunction and to evaluate the reliability of clinical scores of hypo and hyperthyroidism. One hundred ninety-five amiodarone users were submitted to a clinical and laboratory evaluation. Of these, 2.1% were hyperthyroid, 25.1% hypothyroid and 9.2% had only a high T4. Considering thyroid dysfunction variables researched, thyroid autoimmunity was positively associated (OR 4.8; p= 0.02), and male gender had a trend to a positive association (OR 1.86; p= 0.06). Clinical scores were highly sensitive for hyperthyroidism (100%), but not for hypothyroidism (8%). The low prevalence of amiodarone-induced hypothyroidism suggests that this specific region is iodine-sufficient. All patients receiving chronic amiodarone therapy should be checked for clinical scores for hyperthyroidism and laboratory evaluation should be performed, as a screening for thyroid dysfunction, especially if they are male or have positive microsomal antibodies.